Kyai, Pesantren dan Modernitas - M. Zaki Suaidi Zaki (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2022)
Abstract This paper is a theoretical analysis of two dissertations that discuss the character and figures of the kyai from different perspectives and perspectives. The first analysis of Max Weber's theory of leadership in terms of charisma and authority. In theory, modernization and rationalization that take place in pesantren will reduce the influence and charisma of the kyai. The second dissertation also highlights Max Webber's theory of social change in the context of the role of the kyai in bringing about societal change through an empowerment movement in the economic field.